Addition of methyl-β-cyclodextrin loaded with cholesterol (CLC) on the cryopreservation of semen of Holstein Friesian bulls - Viñán Díaz, Hugo Paúl (2020)
The effect of the addition of cholesterol-loaded methyl-β-cyclodextrin (CLC) on the semen cryopreservation of Holstein Friesian bulls was assessed through the assessment of pre and post-freezing seminal characteristics. Four bulls of 3-4 years of age were used and 28 ejaculates were collected. The ejaculates were divided into three aliquots, where the CLC was added: 0, 1.5 and 2 mg of CLC per 120 million sperm cells (T1, T2 and T3 respectively) at 37 °C and incubated for 15 minutes. The samples were refrigerated at 5 °C for 18 hours for stabilization. Semen was frozen in 0.5 ml straws using nitrogen vapours for 7 minutes and then immersed in liquid nitrogen. No statistical differences were found between treatments in all the characteristics of the refrigerated semen. The post-thawing results revealed significant improvements in the cholesterol treatments, obtaining a total motility of 67.73, 79.59 and 74.73%; membrane integrity of 46.89, 60.43 and 55.06%, and vitality of 63.26, 75.84 and 70.53% for T1, T2 and T3, respectively (p<0.05). There were no significant differences between treatments with respect to morphological abnormalities.